INFLUENCE OF POWERLIFTING MEANS ON THE DEVELOPMENT OF PHYSICAL ABILITIES OF 1ST-COURSE STUDENTS - Fomenko, Olena; Peleshenko, Іgor; Razumov, Roman (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This article is devoted to the study of the influence of powerlifting on the development of physical abilities of first-year higher education students. Given the relevance of maintaining physical fitness and psycho-emotional health of students during the period of adaptation to new learning conditions, powerlifting is an effective means of strengthening muscles, improving coordination, strength and endurance. The article examines the main powerlifting exercises, such as squats with a barbell, deadlifts and bench presses, which have a positive effect on the physical development of students, reducing the risk of injuries and improving the functional capabilities of the body. The assessment of the effectiveness of powerlifting classes was carried out through physical testing and comparison of results before and after training. The study showed that regular powerlifting training has a significant impact on the development of physical abilities, increases endurance and stability, and also has a positive effect on the psycho-emotional state of students. The article presents recommendations for optimizing the training process and the importance of powerlifting for improving students' health.